Variasi Genetik Trenggiling Sitaan di Sumatra, Jawa, dan Kalimantan Berdasarkan Control Region DNA Mitokndria (GENETIC VARIATION ON CONFISCATED PANGOLIN OF SUMATRA, JAWA, AND KALIMANTAN BASED ON CONTROL REGION MITOCHONDRIAL DNA) - Wirdateti, Wirdateti; Semiadi, Gono (Jurnal Veteriner; Vol 18 No 2 (2017)DO - 10.19087/jveteriner.2017.18.2.181, 2017)
High levels of illegal trading on Java pangolin ( Manis javanica, Desmarest. 1822 ) for the basic ingredient of Traditional Chinese Medicine have caused sharp decline in its wild population. The purposes of this study were to assess the level of quality and genetic diversity, and to identify the origin of the confiscated individuals by molecular analysis. The original species used as a control were obtained from known areas in Java, Kalimantan, and Sumatera. Molecular analysis was carried out using non-coding region control region (D-loop) of mitochondrial DNA (mtDNA). The results of phylogenic tree analysis showed that 44 confiscated pangolins were from Kalimantan (24 individuals), from Sumatra (seven individuals), and from Java (13 individuals). As many as 19 haplotypes were found on the basis of their base substitutions consisting of nine from Kalimantan, seven from Java and three from Sumatra. Average genetic distance (d) between those from Kalimantan-Java was d = 0.0121 ± 0.0031; those from Borneo-Sumatra was d =0.0123 ± 0.0038 and those from Sumatra-Java was d = 0.0075 ± 0.038, respectively. Overall genetic distance between populations was d = 0.0148 ± 0.0035, with the nucleotide diversity (ð) of 0.0146. These results indicate that over 50% of pangolins seized came from Kaimantan, and Kalimantan populations show a separate group with Java and Sumatra with boostrap 98%. ABSTRAK Tingginya tingkat perburuan trenggiling ( Manis javanica ; Desmarest 1822 ) Indonesia untuk diperdagangkan secara illegal sebagai bahan dasar obat terutama di China, menyebabkan terjadinya penurunan populasi di alam. Tujuan penelitian ini adalah untuk melihat tingkat kualitas dan keragaman genetik trenggiling serta mengetahui asal usul satwa sitaan berdasarkan analisis molekuler. Sebagai kontrol asal usul trenggiling sitaan digunakan sampel alam berdasarkan sebaran populasi yang diketahui pasti yang berasal dari Jawa, Kalimantan, dan Sumatera. Analisis molekuler menggunakan daerah non coding control region (D-loop) mitokondrial DNA (mtDNA). Hasil analisis dari pohon filogeni menunjukkan bahwa dari 44 sampel trenggiling sitaan terindikasi berasal dari Kalimantan sebanyak 24 individu, asal Sumatera tujuh individu, dan dari populasi Jawa 13, sementara rataan jarak genetik (d) antara Kalimantan-Jawa d= 0,0121±0,0031; Kalimantan-Sumatera d= 0,0123±0,0038; dan Sumatera-Jawa d=0,0075±0,038. Jarak genetik secara keseluruhan di antara populasi adalah d= 0,0148±0,0035, dengankeragaman nukleotida (ð) 0,0146. Hasil ini menunjukkan bahwa lebih 50% trenggiling sitaan berasal dari Kalimantan, dan populasi Kalimantan menunjukkan kelompok terpisah dengan Jawa dan Sumatera dengan boostrap 98%.